Pengaruh Orientasi Pasien Baru terhadap Tingkat Kepuasan Pasien - Yeni Kartika Sari (STIKes Patria Husada Blitar, 2014)
The rights of the patients can be fulfiled by nurses through orientation by nurses to new patients. The new patient orientation is a agreement between nurses and patients or families in providing nursing care. The agreement is needed to make a good relationship between nurses and patient or their family. The purpose of this study was to explain the effectiveness of the new patient orientation towards the satisfaction level of nursing care in Melati Room RSD Mardi Waluyo Blitar. Method: Research design was Â experimental research with quasy experimental design Research sample was 30 new patients at Melati Room RSD Mardi Waluyo Blitar were devided equally into two group, namely treatment and control groups at May 24th until May 31st, 2012, its choosed with concecutive sampling. Analysis using Mann Whitney test. Results: The result showed that the level of patient satisfaction on nursing care of treatment groups were 67% satisfied and 33% very satisfied. While the level of patient satisfaction of nursing care of control groups was 80 % satisfied and 20% dissatisfied. There was significant difference in the level of satisfaction of new patients who did and did not the orientation with p-valueÂ 0.00.Â Discussion: It is suggested for nurses to pay attention to the patient satisfaction of nursing care by giving orientation to new patients as nursing intervention.